KATA-KATA PINJAMAN BAHASA INGGRIS DALAM BAHASA INDONESIA PADA KORAN HARIAN TRIBUN MANADO - AMANDA, ZASMITA (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2018)
ABSTRACT Â This research entitled â€œKata-kata Pinjaman Bahasa Inggris dalam Bahasa Indonesia pada Koran Harian Tribun Manadoâ€.Â The objectives of this research are to find out the types and the changes of the meanings of English loan words in Indonesian language. The writer uses the theory of Haugen (1950 : 214) to analyze the data and to find out the types, and Baughâ€™s (1993) theory to get the changes of the meanings. This research has been done by using descriptive method. The writer uses Oxford Dictionary and Kamus Besar Bahasa Indonesia to support the analysis.Â The result of this research shows that there are 109 of loan words which are classified into three kinds of loan word. Based on the theory of Haugen, there are loan word without phonemic substitution, loan word with partial phonemic substitution, and loan word with complete phonemic substitution. The writer only finds two types of the changes of meaning that are, extention of meaning and narrowing of meaning. Â Keyword: Loan Words, Change of Meaning, Sociolinguistic, Tribun Manado Newspaper